The effect of smoking on gingival crevicular fluid levels of myeloperoxidase - Rai Balwant; Kaur Jasdeep; Anand S; Laller Kuldeep (Wolters Kluwer Medknow Publications, 2010)
Objectives : To compare the gingival crevicular fluid (GCF) myeloperoxidase (GM) levels in smokers and non-smokers. Materials and methods : This study comprised 45 subjects: (a) 12 smokers with periodontitis, (b) 10 non-smokers with periodontitis, (c) 11 smokers with healthy periodontium, and (d) 12 non-smokers with healthy periodontium were recruited for the study and their GM levels were analyzed. Results and conclusion : GM levels were significantly higher in smokers with periodontitis compared with others. Hence, more incidence of mutagenesis and cytotoxicity were noted at sites of inflammation mediated by GM in smokers compared with non-smokers.